2017
DOI: 10.5114/pm.2017.68594
|View full text |Cite
|
Sign up to set email alerts
|

Obesity in menopause – our negligence or an unfortunate inevitability?

Abstract: Numerous concerns about menopause exist among women, and fear of an increase in body weight is one of the most important of them. This paper presents an overview of current knowledge concerning the etiology of obesity related to menopause and about the mechanisms of its development, with particular regard to the hormonal changes that occur during this period of life. The role of estrogens in the regulation of energy balance and the effect of sex hormones on metabolism of adipose tissue and other organs are pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
131
0
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(139 citation statements)
references
References 30 publications
2
131
0
6
Order By: Relevance
“…Throughout the menopausal period, women suffer particularly badly from psychological problems. These often concern their body image, upset by the menopausal changes and increased sensitivity to criticism resulting from negative stereotypes of women with obesity [18,19]. Other issues include irritability, mood swings, short-term memory issues, exhaustion, sleep disorders, deep fear manifested in anxiety, dread, and agitation.…”
Section: Objectivementioning
confidence: 99%
“…Throughout the menopausal period, women suffer particularly badly from psychological problems. These often concern their body image, upset by the menopausal changes and increased sensitivity to criticism resulting from negative stereotypes of women with obesity [18,19]. Other issues include irritability, mood swings, short-term memory issues, exhaustion, sleep disorders, deep fear manifested in anxiety, dread, and agitation.…”
Section: Objectivementioning
confidence: 99%
“…The key role in the pathogenesis of obesity in this period of the woman's life belongs to the estrogen deficiency. Estrogens increase fat oxidation in skeletal muscles and inhibit lithogenesis in the liver and muscles [27,29,30]. It has been proven that the deficiency of estrogen causes a reduction in the lipolysis intensity, which leads to the accumulation of adipose tissue, mainly in the anterior abdominal wall and is accompanied by an increase in visceral fatty deposits [25].…”
Section: Analytical Literature Reviewmentioning
confidence: 99%
“…Another important factor contributing to the development of central obesity is a decrease in the secretion of globulin binding sex hormones (ShBg) in the liver, what increases the bioavailability of androgens. It is emphasized that in postmenopausal women the risk of abdominal obesity development is 4.88 times higher than in premenopausal ones [14].…”
mentioning
confidence: 99%
“…Another study showed that the activation of REα stimulates β-adrenergic receptors in visceral tissue and enhances lipolysis, leading to the decrease of adipose tissue in the anterior abdominal wall region. It has been established that estrogens increase fat oxidation in skeletal muscles and inhibit lipogenesis in the liver and muscles [14]. Thus, the deficiency of estrogen, caused by menopause, is accompanied by an increase in visceral fat deposits.…”
mentioning
confidence: 99%